Conceptualizing building information modeling: In construction conflict management - Charehzehi, A.; Yusof, A.; Chai, C.; Chong, Heap Yih (2015)
Conflicts and claims are prevalent features in construction projects and are getting more serious due to the increased size and complexity of the projects nowadays. Innovative, effective and strategic dispute resolution methods should be taken to overcome these issues. The existing practice and agenda of dispute resolution concentrates on cure rather than prevention. Thus, providing new strategies and technologies as management tools is critical to minimize the dispute occurrence. Building information modeling (BIM) is one of the effective techniques that help building in a virtual and collaborative working environment prior to physical construction. This paper aims to initiative a review on the feasible use of BIM for construction conflict management. A conceptual model is developed to analyze and incorporate the philosophy of conflict management into relation to BIM. The model serves as a preliminary reference for resolving the differences or disagreements. It requires further development and incorporates with a proper contract administration for actual implementation in the future.